Trends in incidence of self-harm, neurodevelopmental and mental health conditions among university students compared to the general population: a nationwide electronic data linkage study in Wales - John, Ann; Rouquette, Olivier Y; Lee, Sze Chim; Del Pozo Banos, Marcos (International Journal of Population Data Science, 2025)
Objectives University students are experiencing a significant rise in self-harm and mental health conditions. However, no prior studies have compared their mental health trajectories with those of non-students. This study investigates self-harm, neurodevelopmental disorders, and mental health conditions among students and non-students in Wales over time using routinely collected data. Methods This retrospective cohort study included individuals born between 1987 and 1999 in Wales. Records of university students from the Higher Education Statistics Agency (2012-13 to 2017-18) were linked with demographic and healthcare data observing their characteristics before and during university enrollment. Non-students were pseudo-randomly selected to match the student cohort by age and follow-up duration. Logistic regression calculated the odds of becoming a university student and assessed the drop-out rates among the students, adjusting for demographic, socioeconomic, and health-related factors. Poisson regression estimated the incidence rate ratios for self-harm and mental health conditions, comparing university students and non-students. Results The study included 95,760 students and 151,795 non-students. Females had higher odds of becoming university students than males. Higher deprivation levels and pre-existing self-harm or mental health conditions were linked to lower odds of university entry and a higher risk of dropout. Incidence rates of self-harm, autism spectrum disorder (ASD), depression, schizophrenia, and drug use were lower in students than non-students. However, over time, self-harm, depression, attention-deficit hyperactivity disorder (ADHD), ASD, schizophrenia and alcohol use increased more in students than non-students. Drug use decreased with time in both groups. Students entering university at a later age exhibited increased self-harm and mental health conditions, while students at younger age or in their first year were at higher risk of alcohol misuse compared to non-students. Conclusion This study highlights the common and diverse mental health conditions among students, emphasizing their distinct needs and trajectories compared to non-students. This diversity and complexity of students’ needs requires an integrated person-centred stepped-care approach within universities to better support the mental health and well-being of the student population.